A simple time temperature indicator for real time microbial assessment in minimally processed fruits. (December 2021) - Adiani, Vanshika; Gupta, Sumit; Variyar, Prasad S.
Abstract: Colorimetric time temperature indicator (TTI) which changes colour from colourless to brown due to phenol oxidation in the presence of Na2 CO3 and ammonium per sulphate (APS; free radical initiator) is developed. Twelve TTI prototypes were prepared by using different concentrations of Na2 CO3 (23–59 mM), APS (21–43 mM) with 2% (wt/vol) phenol. Significant (p < 0.05) effect of Na2 CO3 and APS was observed on the activation energy (EaTTI ) of TTI. Activation energy (Eamicrobial ) of microbial spoilage in three minimally processed fruits (pineapple, pomegranate, jackfruit) was evaluated. Colour change of TTI having EaTTI similar to the fruits Eamicrobial demonstrated good correlation (R 2 ≥ 0.7) with microbial growth in all the three fruits. Microbial counts in fruit samples stored under temperature abuse conditions were estimated within an error of ±1 Log10 CFU g −1 by analysing colour change in TTI using DSLR camera. TTI was successfully employed for rapid determination of microbial quality. Highlights: Colorimetric TTI based on phenol oxidation is developed. TTI designed to match the Ea of microbial spoilage for minimally processed fruits. Colour change in TTI correlated with microbial counts in fruits. Camera based assessment of TTI colour change used to estimate microbial counts. The performance of developed TTI is validated at abusive storage conditions.